Tradisi Ziarah Punden: Masyarakat Desa Bumiharjo Kecamatan Guntur Kabupaten Demak - Vadhea Cahyanda Sukma; Izzul Rafiq; Jazila Rizqiya Rahma; Silvi Anggreani; Aulia Miftachul Jannah; Faqihatul Ummah; Arfi Aghisna (Jurnal Pengabdian KOLABORATIF, 2024)
The Real Work Lecture (KKN) experience carried out in Bumiharjo Village really helped us understand and required us to get involved and participate in society directly without any student frills. We gain new learning and knowledge here by participating directly in the community. The theme of strengthening religion is one of the sub-themes that we raised in our group; this was taken into consideration considering the religiousness of the residents in this village. This is proven by the existence of unique religious activities such as a joint pilgrimage to the village punden grave, which is rarely found in other places. The aim of this activity is to illustrate local wisdom in the form of the punden pilgrimage in Bumiharjo Village and to serve as a learning medium for the younger generation to get to know or recognize ulama figures who have contributed to the spread of Islam in the village. The method used is a qualitative literature review method. The results of the activity show that the people of Bumiharjo Village are still enthusiastic about punden activities and are still preserving the tradition of punden pilgrimage.